Permasalahan dan Strategi Pembangunan Lingkungan Berkelanjutan Studi Kasus: Cekungan Bandung - Setiawan Wangsaatmaja; Arwin Sabar; Maria Angela Prasetiati (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no3.20065Environmental problems occurring in the Bandung Basin are resulted from improper management pertaining to land and spatial planning, including landuse policy and control. Arising environmental problems are covering disturbance of watershed hydrological function, surface and groundwater quality and quantity, solid waste, and air quality. Environmental studies in the Bandung Basin have been implemented by landuse change interpretation, surface water regime measurements, water quality, solid waste management, and air quality. Landuse change has occurred where some vegetation areas, such as forests and paddy fi elds, have decreased for 54% in one hand, and developed area has increased into 223% in the other hand. Watershed degradation is indicated by run off coeffi cient increasing from 0.3 in 1950 to 0.55 in 1998. Flow regime has also changed by presence of a maximum extreme discharge increasing tendency from 217.9 m3/sec in 1951 to 285.8 m3/sec in 1998, and minimum extreme discharge decreasing tendency from 6.35 m3/sec in 1951 to 5.7 m3/sec in 1998. Groundwater productivity index continued decreasing from 0.1 million m3/unit in 1900 to 0.0188 million m3/unit in 2002. Environmental problem has also occurred in a solid waste management sector where an average level of service is only 43.7%, and air pollution by motor vehicle and industrial emission, such as PM10, NOx, CO2, SO2, Pb, and acid rain phenomena have also occurred. Fresh water supply level of service in the Bandung Basin only covers 43% of the total needs. Watershed degradation occurring in the Basin needs a management system recovery, administrative based-management that shifted to ecological based integrated watershed management. Effort and strategy required include the policy and institutional reassembling, pollution control, land rehabilitation and conservation, and community empowerment.